A personagem em videogames - Avatar/Persona : no limiar entre o sujeito, a identidade virtual e a ética derridiana - Silva, Aline Conceição Job da (2016)
Currently, video games occupy a prominent place among the popular cultural products and the number of people playing has grown considerably in recent decades. Thus, this thesis sought to understand how the process of identification come about between the player and her character/avatar in the simulated environment of the virtual game through the conditions of (im)possibility and of decidability according to the ethics of Jacque Derrida. Therefore, these processes were analyzed taking into consideration the relations established between the player and the game world through immersion, interaction, and agency; they may result in the construction of a fictional and virtual identity. The Elder Scrolls V: Skyrim and Journey were the analyzed games, because their structure for customization are opposed, since this possibility offers to the gamer the exercise of creating her own character. The bibliography was mainly from Theory of Literature, Game Studies and Philosophy. In addition to the analysis of the games, this thesis evaluated, through a survey, the habits of users and video game genres. The analyses of the games were made through the gameplays of the author of this thesis and from the evaluation of the interactions of players using their gameplays videos available on the internet video channels. The games analyzed allowed to list characteristics that enable the development of fictional and virtual identities, and also narrative, in the game world. The conditions of decidability had two poles: there are enough interactivity and possibilities of choices in The Elder Scrolls V: Skyrim, while in Journey this interaction is low; the conditions of (im)possibility are still well calculated by the gaming systems, then, it is for the subject player to perform singular events in her interaction with the game world. Therefore, the singular events decided and performed by each gamer are the ones that implicate in processess of identification built narratively in the games. “Final” thoughts on the issue are for the future and for further research addressing the cultural relations between players and video games.